THE PARADOX OF KUBROSISWO'S ART IDENTITY: BETWEEN ISLAM AND JAVANESENESS - Setiorini Rahma Safitri (JURNAL PAKARENA, 2022)
This study was motivated by intellectual anxiety about the study of the art of Kubrosiswo. So far, most of the existing studies have focused on the discourse of Islamic identity attached to this art. This study intends to look at the arts in terms of two sides of identity, namely Islamic and Javanese. The method used in this study is a qualitative research method with steps that include: data collection, data validation, analysis, and synthesis. The results of this study show that the art of Kubrosiswo since its birth has brought religious sentiments, in the form of anti-communism. This articulation is manifested in his extra-aesthetic identity which contains elements of Islamic culture, especially from the songs used. Even so, there is another side to this art, especially those that show Javanese characteristics, such as the use of offerings and the presence of a trance session from each performance. This to some extent becomes a kind of paradox of identity for this art.